2021
DOI: 10.1530/joe-20-0388
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling in endocrine and folliculo-stellate cells of the adult pituitary

Abstract: Ubiquitous overactivation of Hedgehog signaling in adult pituitaries results in increased expression of proopiomelanocortin (Pomc), growth hormone (Gh) and prolactin (Prl), elevated adrenocorticotropic hormone (Acth) production and proliferation of Sox2+ cells. Moreover, ACTH, GH and PRL-expressing human pituitary adenomas strongly express the Hedgehog target GLI1. Accordingly, Hedgehog signaling seems to play an important role in pathology and probably also in homeostasis of the adult hypophysis. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Analysis of the correlation between morphometric parameters of GH and FS cells indicated the presence of a statistically significant negative correlation between the average volume density of anterior pituitary FS cells and the nuclear-cytoplasmic ratio of GH cells, suggesting that homeostasis of the growth hormone production/secretion exists [22].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the correlation between morphometric parameters of GH and FS cells indicated the presence of a statistically significant negative correlation between the average volume density of anterior pituitary FS cells and the nuclear-cytoplasmic ratio of GH cells, suggesting that homeostasis of the growth hormone production/secretion exists [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that in vitro the Hedgehog signaling pathway leads FSC to stimulate the production and release of GH by the anterior pituitary, but the production of CXCL12 by FSC can have the same effect [23,24] . By establishing a communication network between the FSC and with the hormone-producing cells, this may correspond in vivo to a physiological reaction mechanism to the increased intake of fatty acids, evident in HFD mice, influencing the expression of FSC [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these studies, our data rather hint towards an indirect hormone regulation by HH signaling in the adult adenohypophysis. We found that HH signaling activation in murine pituitary explants induces Acth , Gh , Prl and Cga expression ( 11 ), whereas a corticotroph-specific Ptch1 or Smo depletion in vivo does not ( 12 ). Moreover, neither corticotrophs nor lactotrophs show active HH signaling in adult mice ( 12 ).…”
Section: Hh Signaling In the Pituitary Glandmentioning
confidence: 93%
“…We found that HH signaling activation in murine pituitary explants induces Acth , Gh , Prl and Cga expression ( 11 ), whereas a corticotroph-specific Ptch1 or Smo depletion in vivo does not ( 12 ). Moreover, neither corticotrophs nor lactotrophs show active HH signaling in adult mice ( 12 ). Interestingly, the FS cell line TtT/GF is responsive to HH signaling activation.…”
Section: Hh Signaling In the Pituitary Glandmentioning
confidence: 93%
See 1 more Smart Citation